Cohesive finite element modeling of the delamination of HTPB binder and HMX crystals under tensile loading. (May 2018) - Walters, David J.; Luscher, Darby J.; Yeager, John D.; Patterson, Brian M.
Highlights: The delamination of HTPB binder from HMX crystals is investigated at an unprecedented level of resolution using CFEM combined with micro-CT. Numerical simulations are brought into agreement with experimental measurements by calibration of cohesive model parameters. Representing the plasticity of binder is important when using a cohesive model for the delamination of a crystal-binder system. Directly modeling the delamination between binder and crystal has utility in development of larger scale simulation of PBX materials. Graphical abstract: Abstract: Accurately modeling the mechanical behavior of the polymer binders and the degradation of interfaces between binder and crystal is important to science-based understanding of the macro-scale response of polymer bonded explosives. The paper presents a description of relatively a simple bi-crystal HMX-HTPB specimen and associated tensile loading experiment including computed tomography imaging, the pertinent constitutive theory, and details of numerical simulations used to infer the behavior of the material during the delamination process. Within this work, mechanical testing and direct numerical simulation of this relatively simple bi-crystal system enabled reasonable isolation of binder-crystal interface delamination, in which the effects of the complicated thermomechanical response of explosive crystals were minimized. Cohesive finite element modeling of the degradation and delamination of the interface between a modified HTPB binder and HMX crystals was used to reproduce observed results from tensile loading experiments on bi-crystal specimens. Several comparisons are made with experimental measurements in order to identify appropriate constitutive behavior of the binder and appropriate parameters for the cohesive traction-separation behavior of the crystal-binder interface. This research demonstrates the utility of directly modeling the delamination between binder and crystal within crystal-binder-crystal tensile specimen towards characterizing the behavior of these interfaces in a manner amenable to larger scale simulation of polycrystalline PBX materials. One critical aspect of this approach is micro computed tomography imaging conducted during the experiments, which enabled comparison of delamination patterns between the direct numerical simulation and actual specimen. In addition to optimizing the cohesive interface parameters, one important finding from this investigation is that understanding and representing the strain-hardening plasticity of HTPB binder is important within the context of using a cohesive traction-separation model for the delamination of a crystal-binder system.